Application of advanced technology in traditional Chinese medicine for cancer therapy - Ke, Gaofeng; Zhang, Jia; Gao, Wufeng; Chen, Jiayi; Liu, Luotong; Wang, Simiao; Zhang, Huan; Yan, Guojun (Frontiers in Pharmacology, 2022)
Although cancer has seriously threatened people's health, it is also identified by the World Health Organization as a controllable, treatable and even curable chronic disease. Traditional Chinese medicine (TCM) has been extensively used to treat cancer due to its multiple targets, minimum side effects and potent therapeutic effects, and thus plays an important role in all stages of tumor therapy. With the continuous progress in cancer treatment, the overall efficacy of cancer therapy has been significantly improved, and the survival time of patients has been dramatically prolonged. In recent years, a series of advanced technologies, including nanotechnology, gene editing technology, real-time cell-based assay (RTCA) technology, and flow cytometry analysis technology, have been developed and applied to study TCM for cancer therapy, which efficiently improve the medicinal value of TCM and accelerate the research progress of TCM in cancer therapy. Therefore, the applications of these advanced technologies in TCM for cancer therapy are summarized in this review. We hope this review will provide a good guidance for TCM in cancer therapy.